2019
DOI: 10.13189/ujph.2019.070201
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice about Transportation of Infectious Substance among Healthcare Providers, Khartoum State

Abstract: Proper shipping of infectious materials is an important practice to prevent healthcare workers (HCWs), other people and environment from spread of biological threats. The main purpose of this study was to determine healthcare providers' knowledge, and practices about transportation of infectious substances. A self-administered designed questionnaire was used to collect relevant data from study respondents. Primary data were double entered and analyzed by using statistical package for social sciences (IBM SPSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Three out of five participants gave correct answers to the questions related to the media of transport for TB samples. In contrast to this, knowledge (25.4%) and practice (15.9%) about transportation of infectious substances among doctors were low in a study from Khartoum state, Sudan [ 12 ]. Another study from north India that focused on specimen collection among the clinicians found deficiencies in the collection and transportation of some extrapulmonary TB samples [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three out of five participants gave correct answers to the questions related to the media of transport for TB samples. In contrast to this, knowledge (25.4%) and practice (15.9%) about transportation of infectious substances among doctors were low in a study from Khartoum state, Sudan [ 12 ]. Another study from north India that focused on specimen collection among the clinicians found deficiencies in the collection and transportation of some extrapulmonary TB samples [ 13 ].…”
Section: Discussionmentioning
confidence: 99%